Sexual dimorphism in myocardial acylcarnitine and triglyceride metabolism. Issue 1 (December 2016) - Devanathan, Sriram; Whitehead, Timothy; Fettig, Nicole; Gropler, Robert; Nemanich, Samuel; Shoghi, Kooresh
Abstract Background Cardiovascular disease is the leading cause of death among diabetic patients. Importantly, recent data highlight the apparent sexual dimorphism in the pathogenesis of cardiovascular disease in diabetics with respect to both frequency- and age-related risk factors. The disposition to cardiovascular disease among diabetic patients has been attributed, at least in part, to excess lipid supply to the heart culminating in lipotoxicity of the heart and downstream derangements. A confounding factor in obese animal models of diabetes is that increased peripheral lipid availability to the heart can induce cardio-metabolic remodeling independent of the underlying pathophysiology of diabetes, thus masking the diabetic phenotype. To that end, we hypothesized that the use of non-obese diabetic (NOD) animal models will reveal metabolic signatures of diabetes in a sex-specific manner. Methods To test this hypothesis, male and female NOD Goto-Kakizaki (GK) rats were used to assess the expression profile of 84 genes involved in lipid metabolism. In parallel, targeted lipidomics analysis was performed to characterize sex differences in homeostasis of non-esterified fatty acids (NEFA), acylcarnitines (AC), and triglycerides (TG). Results Our analysis revealed significant sex differences in the expression of a broad range of genes involved in transport, activation, and utilization of lipids. Furthermore, NOD male rats exhibited enhanced oxidative metabolism and accumulation of TG, whereas female NOD rats exhibited reduced TG content coupled with accumulation of AC species. Multi-dimensional statistical analysis identified saturated AC16:0, AC18:0, and AC20:0 as dominant metabolites in mediating sex differences in AC metabolism. Confocal microscopy of rat cardiomyocytes exposed to AC14:0, AC16:0, and AC18:0 confirmed induction of ROS with AC18:0 being more potent followed by AC14:0. Conclusion Overall, we demonstrate sex differences in myocardial AC and TG metabolism with implications for therapy and diagnosis of diabetic cardiovascular disease.